MORPHOLOGICAL SUBSTITUTION IN THE BOOK AL-’UDAH IN THE SYNTAX OF THE UMDA BY IBN FAROON AL-MADANI (D.5769) - Author (PalArch’s Journal of Archaeology of Egypt / Egyptology, 2021)
The book Al-’Udah fi Arrab Al-Umda is one of the books of the translation of the noble hadith, its author is Sheikh Al-AlamBadr al-Din Abu Muhammad Abdullah bin Muhammad bin Farhoun (d.769 AH). Subjects from this book are issues related to commutation, which I studied after presenting them to the sources of ancient and modern scholars, which are: the substitution of (ta) from (t), (t) from (waw), (waw) from (mim), and (distraction) From (Alfa) and (Alia) from (Distraction), and in this paper we will discuss all the morphological problems related to the subject of substitution.